Broadening, shift and narrowing coefficients in the 2ν4 band of NH3 perturbed by O2, N2 and air. (January 2021) - Maaroufi, N.; Hmida, F.; Tchana, F. Kwabia; Landsheere, X.; Aroui, H.
Highlights: Collisional broadening and shift coefficients as well as Dicke narrowing parameters of 310 lines in the 2 ν 4 band of NH3 perturbed by O2 and N2 have been measured at t  = 295 K. Voigt and soft-collision Galatry profiles were used to fit the measured line shape of each individual transition at various pressures. Measurement of narrowing parameters for about 100 transitions of the 2 ν 4 band. The measured shift coefficients are linear. Air-broadening coefficients were retrieved from the linear combination of O2 - and N2 -broadening coefficients. Abstract: Collisional broadening and shift coefficients as well as Dicke narrowing parameters have been measured at room temperature in the 2 ν 4 band of NH3 perturbed by O2 and N2 for 310 rovibrational lines with rotational quantum numbers 1 ≤  J  ≤ 11 and 0 ≤  K  ≤ 11. The experiments were performed at room temperature with ammonia mixtures in nitrogen and oxygen at different pressures using a high-resolution Fourier transform spectrometer and a mono-spectrum non-linear least squares fitting of Voigt and soft-collision Galatry profiles. Because of Dicke narrowing effect, departure from the Voigt profile is observed that allowed measurement of narrowing parameters for about 100 transitions of the 2 ν 4 band. The collisional broadening coefficients obtained with Galatry profile are larger by about 5% than those derived from Voigt profile . Average absolute accuracies of the measurements are estimated to be 5%, 10% and 14% for broadening, shift and narrowing coefficients, respectively. Air-broadening coefficients were retrieved from the linear combination of O2 - and N2 -broadening coefficients. The results are in good agreement with previous experimental data available in the literature. The whole set of results is given as supplementary material for a possible use in spectroscopic databases.